Comparative investigation of microstructure, mechanical properties and strengthening mechanisms of Al-12Si/TiB2 fabricated by selective laser melting and hot pressing. Issue 15 (15th October 2018) - Xi, L.X.; Zhang, H.; Wang, P.; Li, H.C.; Prashanth, K.G.; Lin, K.J.; Kaban, I.; Gu, D.D.
Abstract: Near-fully dense Al-12Si matrix composites reinforced with TiB2 ceramic particles (2 wt%) were successfully fabricated by selective laser melting (SLM) and hot pressing (HP) of powder mixtures. TiB2 ceramic particles are homogeneously distributed in the Al-12Si matrix at the micrometer-scale owing to a very good wetting between molten Al-12Si alloy and TiB2 ceramic. The microstructural analysis of the as-fabricated SLM samples show the formation of a supersaturated α-Al phase and the decrease of free residual Si with respect to the hot-pressed ones. Both composites exhibit a fine microstructure with a grain size of 5.1 µm and 5.8 µm for SLM- and HP-fabricated samples with addition of TiB2 ceramic particles. The SLM Al-12Si/TiB2 composite exhibits significantly improved microhardness ( 142 ± 6.0 HV0.05 ) and yield strength ( 247 ± 4.0 MPa) compared to the corresponding HP one. Fine cell morphology and nanostructured dispersion strengthening are responsible for the improved mechanical strength of the Al-12Si/TiB2 composite processed by SLM.